Salt hydrogel and preparation method thereof
By using polypropylene amine and hydroxypropyl methylcellulose base materials to embed hygroscopic inorganic salts and carbon materials in the air water adsorbent, an efficient salt hydrogel is prepared, which solves the problem of the small adsorption capacity of existing adsorbents. , desorption difficulties and other problems, achieving efficient, safe and low-cost air water extraction.
Patent Information
- Application Number
- CN202411503792.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
AI Technical Summary
The existing air water intake adsorbents have problems such as small adsorption capacity, difficulty in desorption, complex preparation process and high cost, which limits their application in commercial air water intake.
The bases are used with polypholic and hydroxylopylopyropenyl cellulose, embedded in carbon materials that are embedded in hygroscopic inorganic salts such as LICL and mixed with light thermal conversion. , Prepare high -efficiency salt water gel.
The salt hydrogels of high -wetting multiples, large adsorption capacity, stability, low -relieving driving temperature, and porosity structure are low, and the cost is low, which effectively makes up for the shortcomings of existing adsorption agents.
Smart Images

Figure CN119350659A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogel materials, and in particular to a saline hydrogel and a preparation method thereof. Background Art
[0002] With the rapid growth of the global economy and population, the demand for freshwater resources has risen sharply. However, due to various reasons, freshwater resources are facing a serious shortage. At present, it is difficult to meet the freshwater needs of mankind by traditional means. Air water extraction technology has emerged and has become a hot research topic. For commercial water extraction needs, how to develop efficient, safe and low-cost adsorbents is the main problem in achieving commercial and efficient water extraction. On the one hand, because the water resources obtained by air water extraction are sustainable, it can reduce dependence on traditional water resources. On the other hand, air water extraction technology can be driven by low-temperature heat sources such as solar energy, without consuming a lot of energy, reducing greenhouse gas emissions.
[0003] Air water extraction technology includes different methods, such as adsorption, refrigeration condensation and fogging. The adsorption method is to pass the humid air through the adsorbent, the adsorbent captures the water vapor in the humid air, and further obtains fresh water through evaporation and condensation.
[0004] Common adsorbents on the market include silica gel, fiber adsorbents, molecular sieves, and salt-containing composite adsorbents. However, silica gel is expensive to produce and will deform or melt when exposed to high temperatures. The preparation of molecular sieves requires high temperature and high pressure conditions, and since the adsorption process of molecular sieves is limited by their pores, molecules of a certain size may block the pores, resulting in performance degradation. Compared with hydrogels, the adsorption capacity of fiber adsorbents is limited, and when the fiber adsorbent reaches saturation, regeneration is relatively difficult. The above adsorbents all have some difficult-to-solve problems, such as small adsorption capacity, difficult desorption, complex preparation process, and high cost, which will greatly limit their application and the possibility of commercial water extraction. However, salt-containing composite adsorbents can solve the above problems by introducing hygroscopic inorganic salts and stimulus-responsive components into specific matrices, and are ideal materials for large-scale commercial air water extraction.
[0005] In view of the above problems, it is urgently necessary to provide a hygroscopic salt hydrogel having the following advantages: high moisture absorption rate, large adsorption capacity, stable performance, low desorption driving temperature, stable multi-porous structure and low cost. Summary of the invention
[0006] The purpose of the present invention is to provide a salt hydrogel and a preparation method thereof in view of the deficiencies in the prior art;
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] The present invention provides a method for preparing a saline hydrogel, characterized in that the steps include:
[0009] Step 1, providing carbon material, deionized water, inorganic salt, acrylamide, cellulose or its derivatives, a crosslinking agent, a crosslinking accelerator, and an initiator;
[0010] Step 2, dispersing the carbon material in the deionized water, and sequentially adding the inorganic salt, the acrylamide, the cellulose or its derivative, the crosslinking agent, and the crosslinking accelerator to stir and dissolve to obtain a precursor solution;
[0011] Step 3, adding an initiator to the precursor solution to obtain a foaming mixed solution;
[0012] Step 4: pour the foaming mixed solution into the mold immediately, let it stand for a period of time, and then demould it to obtain a hydrogel sample;
[0013] Step 5, drying and thermally reducing the hydrogel sample in sequence to obtain the saline hydrogel;
[0014] Wherein, the carbon material is selected from at least one of reduced graphene oxide, carboxylated carbon nanotubes, and carbon black;
[0015] Wherein, the cellulose or its derivative is selected from at least one of chitosan, wood cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
[0016] Furthermore, the inorganic salt is selected from at least one of LiCl, MgCl2, and CaCl2.
[0017] Furthermore, the cellulose or its derivative is hydroxypropyl methylcellulose.
[0018] Furthermore, the cross-linking agent is N,N-methylenebisacrylamide, the cross-linking accelerator is N,N,N',N'-tetramethylethylenediamine, and the initiator is ammonium persulfate.
[0019] Furthermore, in the step 2, the method of dispersing the carbon material in the deionized water is ultrasonic dispersion, and the stirring and dissolving step after adding the inorganic salt, the acrylamide, the cellulose or its derivative, the crosslinking agent, and the crosslinking accelerator includes: low-temperature water bath magnetic stirring, and high-speed stirring; wherein,
[0020] The ultrasonic dispersion time of the ultrasonic dispersion is 1min-20min;
[0021] The rotation speed of the low-temperature water bath magnetic stirring is 500rpm-600rpm;
[0022] The temperature of the low-temperature water bath magnetic stirring is 0°C-10°C;
[0023] The stirring time of the low-temperature water bath magnetic stirring is 5 min-10 min.
[0024] Furthermore, in the step 2, after the precursor solution is magnetically stirred in a low-temperature water bath, the precursor solution is stirred using a cantilevered powerful electric stirrer; wherein,
[0025] The rotation speed of the high-speed stirring is 1700rmp-1900rmp;
[0026] The stirring time of the high-speed stirring is 10 min-30 min.
[0027] Furthermore, in step 5, the drying method is to use an air drying oven for drying, and the thermal reduction method is to use a vacuum oven for thermal reduction; wherein,
[0028] The drying process lasts for 7-9 hours.
[0029] The drying treatment temperature is 70°C-100°C;
[0030] The heat reduction treatment time is 7h-9h;
[0031] The treatment temperature of the thermal reduction is 110-130°C.
[0032] Furthermore, in the step 1,
[0033] The amount of the carbon material used is 1 mg-40 mg; the amount of the deionized water used is 1 mL-15 mL;
[0034] The dosage of the inorganic salt is 1g-10g;
[0035] The amount of acrylamide used is 1g-5g;
[0036] The amount of cellulose or its derivatives is 0.1g-0.5g;
[0037] The amount of the cross-linking agent is 1mg-10mg;
[0038] The amount of the cross-linking accelerator is 1 μL-15 μL;
[0039] The dosage of the initiator is 1 mg to 15 mg.
[0040] A salt hydrogel prepared by the preparation method as described above.
[0041] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:
[0042] The present invention uses polyacrylamide and hydroxypropyl methylcellulose as a substrate, embeds a hygroscopic inorganic salt as an adsorbent and dopes a carbon material for photothermal conversion. By adjusting the ratio between the components and selecting a suitable preparation process, it is possible to achieve strong hygroscopic ability, large adsorption capacity, no liquid decomposition phenomenon, strong recyclability, and faster adsorption / desorption kinetics, effectively making up for the shortcomings of commonly used air water extraction adsorbents. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The figure is a schematic diagram of the preparation process of the salt hydrogel preparation method;
[0044] Figure 2 This is a graph showing the adsorption and desorption performance test results per unit weight (g / g) of salt hydrogel;
[0045] Figure 3 is the unit area of salt hydrogel (g / m 2 )'s adsorption and desorption performance test results;
[0046] Figure 4 It is the moisture absorption isotherm of saline hydrogel under different humidity conditions;
[0047] Figure 5 This is a graph showing the cyclic durability test results of saline hydrogel;
[0048] Figure 6 This is the effect of different mass proportions of LiCl in saline hydrogel on its hygroscopic properties. DETAILED DESCRIPTION
[0049] The specific embodiments of the present invention will be described in detail below.
[0050] Unless otherwise defined, technical or scientific terms used in the claims and the specification shall have the common meanings understood by persons having ordinary skills in the technical field to which the present invention belongs.
[0051] The words "include" or similar words used in the patent application specification and claims of the present invention mean that the items appearing before "include" include the items listed after "include" or their equivalents, and do not exclude other items.
[0052] The numerical values mentioned in the present invention include all numerical values that increase from low to high by one unit, assuming that there are at least two units between any lower value and the higher value. For example, if a component or a physical quantity is said to be from 1 to 100, 10 to 90 is more preferred, and 20 to 80 is the most preferred, it is intended to express that values such as 5 to 95, 14 to 76, 23 to 67, 32 to 58, 41 to 49 are clearly listed in this specification; for values less than 1, 0.0001, 0.001, 0.01 or 0.1 are considered to be more suitable as a unit. The above examples are for illustrative purposes only. In fact, all numerical combinations between the lowest value and the highest value listed are deemed to be clearly listed in this specification in a similar manner.
[0053] Example 1
[0054] This embodiment provides a salt hydrogel and a preparation method thereof. In this embodiment, polyacrylamide PAM and hydroxypropyl methylcellulose are used as a substrate, LiCl is embedded as a hygroscopic inorganic salt and a photothermal conversion component, reduced graphene oxide (rGO) is doped. The components are used in a suitable ratio and preparation process to prepare a salt hydrogel that can be used for commercial efficient water extraction. The preparation method thereof comprises the following steps:
[0055] Step 1: providing reduced graphene oxide, deionized water, inorganic salt, acrylamide, cellulose or its derivatives, N,N-methylenebisacrylamide, N,N,N',N'-tetramethylethylenediamine, and ammonium persulfate.
[0056] Wherein, the inorganic salt is LiCl, and the cellulose or its derivative is hydroxypropyl methylcellulose;
[0057] Step 2, weigh 35 mg of reduced graphene oxide and ultrasonically disperse it in 10 ml of deionized water, the ultrasonic dispersion time is 10 min, and the reduced graphene oxide dispersion is obtained, then 5 g of anhydrous LiCl is weighed, added to the reduced graphene oxide dispersion, and the water bath magnetic stirrer is stirred at a low speed, wherein the speed of the low-speed stirring is 500 rpm, and then the low-speed stirring is performed until the anhydrous LiCl is completely dissolved to obtain a mixed solution of reduced graphene oxide and anhydrous lithium chloride;
[0058] Step 3, weigh 2g of acrylamide powder and add it to the mixed solution, stir at low speed until it is completely dissolved, and obtain a first mixed solution, weigh 0.25g of hydroxypropyl methylcellulose powder and slowly add it to the first mixed solution, stir at low speed until it is completely dissolved, and obtain a second mixed solution, weigh 6mg of cross-linking agent N,N-methylenebisacrylamide and add it to the second mixed solution, stir at low speed until it is completely dissolved, and obtain a third mixed solution, then add 10μL of cross-linking promoter tetramethylethylenediamine, and stir evenly at low speed to obtain a fourth mixed solution, stir the fourth mixed solution at low speed for 5min, and then use a cantilevered high-powered electric stirrer to adjust the speed to 1800rmp and stir at high speed for 20min to obtain a precursor solution.
[0059] Step 4: Add 9 mg of initiator ammonium persulfate and evenly drop it into the precursor solution. After stirring for 1 minute, immediately pour the obtained foaming mixed solution into the prepared mold for molding. After standing for a period of time, demold the solution to obtain a hydrogel sample.
[0060] Step 5: Place the demoulding hydrogel sample in a forced air drying oven for drying, and transfer the dried hydrogel sample to a vacuum oven for thermal reduction to obtain a saline hydrogel.
[0061] In this embodiment, the PHGL hydrogel obtained was tested for its moisture absorption performance, and the test results were as follows: moisture absorption was carried out under the conditions of 25°C and 75% RH for 10 hours, and each gram of dry material could absorb 1.32 g of water vapor in the air; then desorption was carried out under the conditions of 80°C and 7% RH, and the amount of water taken up per gram of dry material was 1.14 g, with a water absorption rate of 86%.
[0062] Example 2
[0063] This embodiment provides a salt hydrogel and a preparation method thereof. In this embodiment, polyacrylamide and hydroxypropyl methylcellulose are used as a substrate, LiCl is embedded as a hygroscopic inorganic salt, and carboxylated carbon nanotubes as a photothermal conversion component are doped. The components are used in a suitable ratio and preparation process to prepare a salt hydrogel that can be used for commercial efficient water extraction. The preparation method thereof comprises the following steps:
[0064] Step 1: providing carboxylated carbon nanotubes, deionized water, inorganic salts, acrylamide, cellulose or its derivatives, N,N-methylenebisacrylamide, N,N,N',N'-tetramethylethylenediamine, and ammonium persulfate.
[0065] Wherein, the inorganic salt is LiCl, and the cellulose or its derivative is hydroxypropyl methylcellulose;
[0066] Step 2: Weigh 4.5 mg of carboxylated carbon nanotubes and ultrasonically disperse them in 3 ml of deionized water for 10 min to obtain a carboxylated carbon nanotube dispersion. Then weigh 1.51 g of anhydrous LiCl and add it to the carboxylated carbon nanotube dispersion. Stir the mixture with a water bath magnetic stirrer at a low speed of 500 rpm until the anhydrous LiCl is completely dissolved to obtain a mixed solution of carboxylated carbon nanotubes and anhydrous lithium chloride.
[0067] Step 3, weigh 2g of acrylamide powder and add it to the mixed solution, stir at low speed until it is completely dissolved, and obtain a first mixed solution, weigh 0.25g of hydroxypropyl methylcellulose powder and slowly add it to the first mixed solution, stir at low speed until it is completely dissolved, and obtain a second mixed solution, weigh 6mg of cross-linking agent N,N-methylenebisacrylamide and add it to the second mixed solution, stir at low speed until it is completely dissolved, and obtain a third mixed solution, then add 10μL of cross-linking promoter tetramethylethylenediamine, and stir evenly at low speed to obtain a fourth mixed solution, stir the fourth mixed solution at low speed for 5min, and then use a cantilevered high-powered electric stirrer to adjust the speed to 1800rmp and stir at high speed for 20min to obtain a precursor solution.
[0068] Step 4: Add 9 mg of initiator ammonium persulfate and evenly drop it into the precursor solution. After stirring for 1 minute, immediately pour the obtained foaming mixed solution into the prepared mold for molding. After standing for a period of time, demold the solution to obtain a hydrogel sample.
[0069] Step 5: Place the demoulding hydrogel sample in a forced air drying oven for drying, and transfer the dried hydrogel sample to a vacuum oven for thermal reduction to obtain a saline hydrogel.
[0070] Example 3
[0071] This embodiment provides a salt hydrogel and a preparation method thereof. In this embodiment, polyacrylamide and hydroxypropyl methylcellulose are used as a substrate, LiCl is embedded as a hygroscopic inorganic salt and carbon black, a photothermal conversion component, is doped, and the components are used in a suitable ratio and preparation process to prepare a salt hydrogel that can be used for commercial efficient water extraction. The preparation method thereof comprises the following steps:
[0072] Step 1: Provide carbon black, deionized water, inorganic salt, acrylamide, cellulose or its derivatives, N,N-methylenebisacrylamide, N,N,N',N'-tetramethylethylenediamine, and ammonium persulfate.
[0073] Wherein, the inorganic salt is LiCl, and the cellulose or its derivative is hydroxypropyl methylcellulose;
[0074] Step 2: Weigh 10 mg of carbon black and disperse it in 10 ml of deionized water. The ultrasonic dispersion time is 10 min to obtain a carbon black dispersion. Then weigh 5 g of anhydrous LiCl and add it to the carbon black dispersion. Stir the mixture with a water bath magnetic stirrer at a low speed of 500 rpm until the anhydrous LiCl is completely dissolved to obtain a mixed solution of carbon black and anhydrous LiCl.
[0075] Step 3, weigh 2g of acrylamide powder and add it to the mixed solution, stir at low speed until it is completely dissolved, and obtain a first mixed solution, weigh 0.25g of hydroxypropyl methylcellulose powder and slowly add it to the first mixed solution, stir at low speed until it is completely dissolved, and obtain a second mixed solution, weigh 6mg of cross-linking agent N,N-methylenebisacrylamide and add it to the second mixed solution, stir at low speed until it is completely dissolved, and obtain a third mixed solution, then add 10μL of cross-linking promoter tetramethylethylenediamine, and stir evenly at low speed to obtain a fourth mixed solution, stir the fourth mixed solution at low speed for 5min, and then use a cantilevered high-powered electric stirrer to adjust the speed to 1800rmp and stir at high speed for 20min to obtain a precursor solution.
[0076] Step 4: Add 9 mg of initiator ammonium persulfate and evenly drop it into the precursor solution. After stirring for 1 minute, immediately pour the obtained foaming mixed solution into the prepared mold for molding. After standing for a period of time, demold the solution to obtain a hydrogel sample.
[0077] Step 5: Place the demoulding hydrogel sample in a forced air drying oven for drying, and transfer the dried hydrogel sample to a vacuum oven for thermal reduction to obtain a saline hydrogel.
[0078] As a preferred embodiment, cellulose or a derivative thereof is selected from at least one of chitosan, lignocellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose.
[0079] As a preferred embodiment, the inorganic salt is selected from at least one of MgCl2 and CaCl2.
[0080] The present invention uses polyacrylamide and hydroxypropyl methylcellulose as a substrate, embeds a hygroscopic inorganic salt as an adsorbent and dopes a carbon material for photothermal conversion. By adjusting the ratio between the components and selecting a suitable preparation process, it is possible to achieve strong hygroscopic ability, large adsorption capacity, no liquid decomposition phenomenon, strong recyclability, and faster adsorption / desorption kinetics, effectively making up for the shortcomings of commonly used air water extraction adsorbents.
[0081] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a saline hydrogel, characterized in that the steps include: Step 1, providing carbon material, deionized water, inorganic salt, acrylamide, cellulose or its derivatives, a crosslinking agent, a crosslinking accelerator, and an initiator; Step 2: dispersing the carbon material in the deionized water, and sequentially adding the inorganic salt, the acrylamide, the cellulose or its derivative, the crosslinking agent, and the crosslinking accelerator to stir and dissolve to obtain a precursor solution; Step 3, adding an initiator to the precursor solution to obtain a foaming mixed solution; Step 4: pour the foaming mixed solution into the mold immediately, let it stand for a period of time, and then demould it to obtain a hydrogel sample; Step 5, drying and thermally reducing the hydrogel sample in sequence to obtain the saline hydrogel; Wherein, the carbon material is selected from at least one of reduced graphene oxide, carboxylated carbon nanotubes, and carbon black; Wherein, the cellulose or its derivative is selected from at least one of chitosan, wood cellulose, methyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
2. The preparation method according to claim 1, characterized in that: The inorganic salt is selected from at least one of LiCl, MgCl2, and CaCl2.
3. The preparation method according to claim 1, characterized in that: The cellulose or its derivative is hydroxypropyl methylcellulose.
4. The preparation method according to claim 1, characterized in that: The cross-linking agent is N,N-methylenebisacrylamide, the cross-linking accelerator is N,N,N',N'-tetramethylethylenediamine, and the initiator is ammonium persulfate.
5. The preparation method according to claim 1, characterized in that: In the step 2, the method of dispersing the carbon material in the deionized water is ultrasonic dispersion, and the stirring and dissolving steps after adding the inorganic salt, the acrylamide, the cellulose or its derivative, the crosslinking agent, and the crosslinking accelerator include: low-temperature water bath magnetic stirring, and high-speed stirring; wherein, The ultrasonic dispersion time of the ultrasonic dispersion is 1min-20min; The rotation speed of the low-temperature water bath magnetic stirring is 500rpm-600rpm; The temperature of the low-temperature water bath magnetic stirring is 0°C-10°C; The stirring time of the low-temperature water bath magnetic stirring is 5 min-10 min.
6. The preparation method according to claim 1, characterized in that: In the step 2, after the precursor solution is magnetically stirred in a low-temperature water bath, the precursor solution is stirred using a cantilevered powerful electric stirrer; wherein, The rotation speed of the high-speed stirring is 1700rmp-1900rmp; The stirring time of the high-speed stirring is 10 min-30 min.
7. The preparation method according to claim 1, characterized in that: In the step 5, the drying method is to use a blast drying oven for drying, and the thermal reduction method is to use a vacuum oven for thermal reduction; wherein, The drying process lasts for 7-9 hours. The drying treatment temperature is 70°C-100°C; The heat reduction treatment time is 7h-9h; The treatment temperature of the thermal reduction is 110-130°C.
8. The preparation method according to claim 1, characterized in that: In the step 1, The amount of the carbon material used is 1 mg-40 mg; the amount of the deionized water used is 1 mL-15 mL; The dosage of the inorganic salt is 1g-10g; The amount of acrylamide used is 1g-5g; The amount of cellulose or its derivatives is 0.1g-0.5g; The amount of the cross-linking agent is 1mg-10mg; The amount of the cross-linking accelerator is 1 μL-15 μL; The dosage of the initiator is 1 mg to 15 mg.
9. A saline hydrogel prepared by the preparation method according to any one of claims 1 to 8.